2007
DOI: 10.1007/s11427-007-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a recombinant fowlpox virus containing HIV-1 multi-epitope-p24 chimeric gene in mice

Abstract: The epidemic of HIV/AIDS is sweeping across the world. It is of great importance to figure out new ways to curb this disease. Epitope-based vaccine is one of these solutions. In this study, a chimeric gene was obtained by combination of a designed HIV-1 multi-epitope gene (MEG) and HIV-1 p24 gene. A recombinant plasmid pUTA2-MEGp24 was then constructed by inserting MEGp24 gene into the downstream of the promoter (ATI-P7.5x20) of fowlpox virus (FPV) transfer vector pUTA2. The recombinant plasmid and wild-type F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The mixture was incubated in the dark at 4 • C for 30 min and then washed twice, followed by addition of 1.0 mL of PBS. The stained cells were detected by flow cytometry to count the T lymphocytes [13,14].…”
Section: Detection Of Cd4 + and Cd8 + T Lymphocytes In Peripheral Bloodmentioning
confidence: 99%
“…The mixture was incubated in the dark at 4 • C for 30 min and then washed twice, followed by addition of 1.0 mL of PBS. The stained cells were detected by flow cytometry to count the T lymphocytes [13,14].…”
Section: Detection Of Cd4 + and Cd8 + T Lymphocytes In Peripheral Bloodmentioning
confidence: 99%
“…DNA vaccines have a significant advantage in the ability to elicit the CTL response (Herd et al, 2007;Molder et al, 2009). Moreover, the recombinant modified vaccinia virus Ankara (Ondondo et al, 2006;Wyatt et al, 2008) and recombinant FPV (Zhang et al, 2007;Emery et al, 2007) were reported to express HIV-1 proteins that elicited CTLmediated responses after the immunization.…”
Section: Discussionmentioning
confidence: 99%
“…16 Another example is the late ATI promoter (driving the A25L ORF), found in both VACV and cowpox virus. 29 The cowpox ATI promoter was utilised successfully in recombinant FPV 30 and MVA. 31 However, if the level of expression is very critical, a comparison should be performed to assess the activity of cross-stain exogenous promoters.…”
Section: Introductionmentioning
confidence: 99%